(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
This article investigates major theoretical perspectives on the prosaic stroph (or prosaic stanza) as a complex syntactic construction that operates at the intersection of sentence grammar and discourse structure. Scholars have long debated how extended syntactic units such as the period, paragraph-sentence, and stroph contribute to textual cohesion and rhythm in prose. The review traces the evolution of these concepts from classical rhetoric to modern linguistics, highlighting the structural, semantic, and functional dimensions of the prosaic stroph. Attention is given to its relationship with the period, mechanisms of cohesion, rhythm, and its communicative role in literary and academic discourse. The synthesis underscores the prosaic stroph as an essential unit for understanding stylistic and cognitive organization in language.